Uma crítica à judicialização da saúde a partir do conceito do justo aristotélico - Guarnieri, Luciano Morgado (2023)
This dissertation is part of the research line Ethics, Language and Justice, which is part of the master's program in Law at the Pontifical Catholic University of São Paulo. The text aims to analyze the structure and legal classifications of health protection in the Brazilian constitutional system and, therefore, evaluate the intervention of the Judiciary in this system in the light of the Aristotelian concept of fairness. Qualitatively, through research directed to the bibliography at the end listed, the theme has its development based on three fundamental complements: the understanding of the classic concept of justice according to Aristotle, considering other classic concepts and the development of constitutional protection to health; the analysis of individualist thought and the observation of social vulnerability based on the theory of biopolitics by Foucault and Achille Mbembe; finally, a reflection on the interference of the Judiciary in matters related to public policies in the scenario of social inequality/vulnerability in the light of the Aristotelian concept of fairness. Aristotle's classic texts related to justice are the theoretical framework of this work. Based on this framework, it is possible to verify, through the critical-analytical method, the possible injustice in the interference of the Judiciary in matters specific to public policies, especially with regard to health protection